Designing neurotransmitter dopamine-functionalized naphthalene diimide molecular architectures for high-performance organic supercapacitor electrode materials. (15th April 2021) - Biradar, Madan R.; Salkar, Akshay V.; Morajkar, Pranay P.; Bhosale, Sheshanath V.; Bhosale, Sidhanath V.
Abstract : Naphthalenediimide-dopamine conjugates were successfully synthesized, and the influence of dopamine, a neurotransmitter, on the supercapacitor properties of a NDI scaffold was explored. Abstract : Redox-active small organic molecules have recently gained immense interest as electrode materials for supercapacitor device applications. Such redox-active molecular architectural manipulation offers an exciting opportunity to modify charge storage properties. However, increasing the electrochemical characteristics of these materials via structural modification remains a challenge. Surprisingly, naphthalene diimides (NDI s) are planar aromatic molecules that exhibit n-type semiconducting properties but are not much explored in the field of supercapacitors (SCs). Herein, we present the design and synthesis of NDI and its derivatives functionalised with dopamine (DP) at imide positions i.e . NDI, NDI with 1DP and NDI with 2DP at both the imides. We also studied their application as composite electrode materials for supercapacitors. The resulting NDI-2DP /CP electrode exhibited a significant increase in specific capacitance of 202.5 F g −1 (cyclic voltammetry, CV) and 195.9 F g −1 (galvanostatic charge/discharge, GCD) when compared to NDI-1DP /CP (142.8 F g −1, CV; and 137.2 F g −1, GCD) and NDI /CP (45.6 F g −1, CV; and 37.6 F g −1, GCD) in a potential window of 0 V to 1 V. NDI-2DP /CP displayed excellent stability up to 10 000 charge/discharge cycles and almost 96% retention of the initial capacitance in a three-electrode configuration setup. NDI-2DP /CP-, NDI-1DP /CP- and NDI /CP-based symmetric solid-state two-electrode SCs were also fabricated, among which the SC device comprising NDI-2DP /CP showed a specific capacitance of 83.1 F g −1 (CV) at a scan rate of 5 mV s −1 and 73.1 F g −1 (GCD) at a current density of 0.5 A g −1 . Present results indicate that NDI-2DP /CP could serve as a promising electrode material for commercial applications.